2022
DOI: 10.1002/ptr.7528
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin protects against myocardial ischemic by inhibiting oxidative stress, apoptosis, and L‐type Ca2+ channels

Abstract: Liquiritigenin (Lq) offers cytoprotective effects against various cardiac injuries, but its beneficial effects on myocardial ischemic (MI) injury and the related mechanisms remain unclear. In the in vivo study, an animal model of MI was induced by intraperitoneal injection of isoproterenol (Iso, 85 mg/kg). ECG, heart rate, serum levels of CK and CK‐MB, histopathological changes, and reactive oxygen species (ROS) levels were all measured. In vitro, H9c2 cells were divided into four groups and treated for 24 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Metabolites of licorice flavonoids and 6-gingerol were also mainly detected. Liquiritigenin offers cytoprotective effects against various cardiac injuries, and it could protect against myocardial ischemic injury by antioxidation, antiapoptosis, counteraction mitochondrial dysfunction, and damping intracellular Ca 2+ [ 43 ]. 6-Gingerol was identified as a novel angiotensin II type 1 receptor antagonist for cardiovascular disease by high-throughput screening, which partially clarified the mechanism of ginger regulating blood pressure and strengthening the heart [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metabolites of licorice flavonoids and 6-gingerol were also mainly detected. Liquiritigenin offers cytoprotective effects against various cardiac injuries, and it could protect against myocardial ischemic injury by antioxidation, antiapoptosis, counteraction mitochondrial dysfunction, and damping intracellular Ca 2+ [ 43 ]. 6-Gingerol was identified as a novel angiotensin II type 1 receptor antagonist for cardiovascular disease by high-throughput screening, which partially clarified the mechanism of ginger regulating blood pressure and strengthening the heart [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…DFV is a flavonoid compound widely present in Chinese herbal medicines such as PR, Glycyrrhizae radix et rhizome (Pharmacopoeia of China, 2015), Isatidis folium (Pharmacopoeia of China, 2015), Hedysari Radix (Pharmacopoeia of China, 2015), Epimedii folium (Pharmacopoeia of China, 2015), etc. The liver- and heart-protective effects of DFV have been extensively studied [ 26 , 73 , 74 , 75 ]. In addition, there have been some reports on the neuroprotective effects of DFV that we are concerned about.…”
Section: Discussionmentioning
confidence: 99%
“…DFV belongs to the flavonoid compounds in PR. Previous studies have shown that DFV has liver protection [ 25 ], anti-myocardial ischemia [ 26 ], anti-breast cancer [ 27 ], and bone protection effects [ 28 , 29 ]. In these studies, DFV demonstrated strong anti-inflammatory and antioxidant stress-resistance abilities.…”
Section: Introductionmentioning
confidence: 99%
“…As a clinically marketed drug, SGI has shown curative effects in clinical experiments ( Sun et al, 2017 ). Oxidative damage is an important pathophysiological basis for the occurrence and development of MI ( Zhang M. et al, 2022 ). In this study, we found that the effects of SGI against MI occur through inhibitin of oxidative stress and apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%